Life Insurance in Maritime Labour Agreement as Legal Protection and Certainty for Fishermen - Christin Septina Basani (Dialogia Iuridica, 2022)
Fishermen in working with weather, climate and sea wave problems, which are determinants of the catch, including the risk of life which causes necessity of insurance. The government has been holding fisheries insurance which aimed at fishermen, fish raisers and salt farmers. In addition, there is life insurance for catching fish fishermen. Unfortunately, not all fishermen sign up for the insurance. On average, follow this insurance. On average, those who particip ate in life insurance, are fishermen whohave vessels with a capacity above 20 GT (gross tonnage), while for vessels measuring 30 GT can employ 15-20 crew members. The fact that fishermen’s welfare must be prioritized has made the government issue Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers and Salt Farmers. This law relates to welfare and legal protection for fishermen, where the rights of fishermen are to seek welfare for their lives. Guarantees for fishermen participating in life insurance can be included in the Sea Work Agreement where ship owners or companies and fishing workers who work have an awareness of safety, welfare, and a decent life as the state’s objectives as stipulated in the 1945 Constitution and Pancasila. To improve economic viability, especially for fishing workers, the government's role should focus on the welfare of labor fishermen as a further step from Law Number 7 of 2016 which regulates fisheries insurance or life insurance for fishermen. This research is conducted in Regency of Indramayu, using literature study, statute, and conceptual approach.